Activation Energy of Copper Benzotriazole System in Sulphuric Acid Containing Chloride - K. Singh, Arvind; Singh, B.K. (Asian Journal of Chemistry, 2016)
The value of activation energy is low for corroding processes and high in case of inhibition. But it becomes very high when a corrosion accelerator like chloride is used.